Color Lexicon and Its Cultural Implications - Rasulova Shahnoza Abduvasi qizi (Peerian Journals Publishing, 2024)
This text explores the multifaceted role of color designations within language and culture, emphasizing how colors serve as powerful symbols and carriers of meaning. It examines how different cultures interpret and use colors to express emotions, values, and social concepts. The study covers the universal and culturally specific aspects of color symbolism, highlighting similarities and differences in color meanings across various societies
Keywords: Color; Language; Culture